2019
DOI: 10.1016/j.echo.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Segmental Strain Analysis in Pediatric Left Ventricular Noncompaction Cardiomyopathy

Abstract: Background: Left ventricular noncompaction cardiomyopathy (LVNC) is characterized by prominent left ventricular trabeculations, often leading to myocardial dysfunction and death or heart transplantation. Although diagnostic echocardiographic criteria exist for LVNC, segmental speckle-tracking strain patterns have not been described in pediatric LVNC. The objectives of this study were to characterize segmental noncompaction, evaluate segmental speckle-tracking strain, and characterize peak strain values in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
6
12
0
2
Order By: Relevance
“…In studying the mean segmental strain values of the apical, mid and basal regions, we found an increase in segmental strain values from base to apex, which has been previously described in healthy adults; however, our results were slightly different, namely, the mid part had the best longitudinal strain value, which may be due to the small number of included patients [34]. Previous CMR and speckle-tracking echocardiography studies have mentioned that these regional strain differences disappear in patients with DCM, and in accordance with this, we also observed that the decrease in segmental strains affected all three parts of the LV in LVNC patients with a reduced EF [27,35]. Furthermore, an opposite pattern was exhibited in this LVNC patient group; namely, the apical longitudinal strain became the worst of the three parts, which was previously described in different DCM and LVNC populations with a severely reduced EF [11,12].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In studying the mean segmental strain values of the apical, mid and basal regions, we found an increase in segmental strain values from base to apex, which has been previously described in healthy adults; however, our results were slightly different, namely, the mid part had the best longitudinal strain value, which may be due to the small number of included patients [34]. Previous CMR and speckle-tracking echocardiography studies have mentioned that these regional strain differences disappear in patients with DCM, and in accordance with this, we also observed that the decrease in segmental strains affected all three parts of the LV in LVNC patients with a reduced EF [27,35]. Furthermore, an opposite pattern was exhibited in this LVNC patient group; namely, the apical longitudinal strain became the worst of the three parts, which was previously described in different DCM and LVNC populations with a severely reduced EF [11,12].…”
Section: Discussionsupporting
confidence: 72%
“…In our study, we found that the GLS, GCS and GRS gradually decreased as LV function worsened. The decreased strains in all three directions suggest that LVNC is a complex structural disease that affects not only the noncompacted but the compacted layer as well [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that longitudinal strain of the apical region was impaired in LVNC even when compared to dilated and hypertrophic cardiomyopathies [13][14][15][16]23,24]. Such impairment of longitudinal strain was noticed in compacted and non-compacted segments of LVNC ventricles [13,23,24]. Similar results were obtained in a paediatric population including reduced circumferential and radial strain [23].…”
Section: Global and Regional Strainsupporting
confidence: 62%
“…Regional assessment of strain by segmental analysis can be a promising tool to study systolic function in cardiomyopathies such as LVNC. Recent studies showed that longitudinal strain of the apical region was impaired in LVNC even when compared to dilated and hypertrophic cardiomyopathies [13][14][15][16]23,24]. Such impairment of longitudinal strain was noticed in compacted and non-compacted segments of LVNC ventricles [13,23,24].…”
Section: Global and Regional Strainmentioning
confidence: 99%
“…Strain measurements were lowest in those with adverse compared with favorable outcomes. In NCCM, deformation was affected in all regions, including compacted myocardial segments [ 79 ].…”
Section: Diagnostic Criteriamentioning
confidence: 99%